Factors Contributing to Environmentally Friendly Business Practices in SMEs (Small and Medium Enterprises) With a Focus on Process Performance and Resources: Study of Local Culinary SMEs in North Kuin Village, South Kalimantan, Indonesia - Anisah, Hastin Umi; Wimby Wandary; Ariyani Wahyu Wijayanti (HM Publisher, 2024)
Environmentally friendly business practices (PBR) are often overlooked by small and medium enterprises (SMEs), even though they are proven to provide competitive advantages, reduce risks, encourage environmental sustainability, and increase organizational efficiency. This research analyzes the factors that influence PBR in local culinary SMEs, with a focus on process performance (PP) and SME resources. This research uses a quantitative approach with structural equation modeling (SEM) to analyze the influence of process performance (PP) and SME resources (fundamental resources (FR), upgrading capability (UC), and dynamic capabilities (DC)) on PBR in local culinary SMEs in North Kuin Village, South Kalimantan. The research results show that only fundamental resources (FR) and improvement capabilities (UC) influence PBR in local culinary SMEs. SMEs with access to resources and the ability to increase capacity have more potential to implement PBR.